The Development of Participatory Learning Resource for Pottery Handicraft in Banpatan Community, San Phak Wan Sub-District, Hang Dong District, Chiang Mai Province - Mungtha, Rungthip; Wises, Sahathaya; Yesuwan, Tipaporn (MCU Haripunchai Review, 2026)
The objectives of research are: 1) To study the historical development and knowledge of pottery handicrafts in Banpatan community 2) To develop a pottery handicraft learning center through community participation and 3) To propose guidelines for promoting a pottery handicraft learning center with community involvement. This study is qualitative research. The research’s target groups comprised community leaders, representatives from government agencies, community members, pottery artisans, and pottery business operators. Research instruments included structured interview forms and in-depth interviews, conducted with 5 participants from each of the five target groups, totaling 25 participants. Furthermore, a community focus group discussion was organized with 10 representatives drawn from the five groups. The collected data were analyzed through content analysis. The research results indicated that: 1) The historical development and knowledge of pottery handicrafts in Banpatan community found that the tradition of pottery-making has evolved continuously for over a century. It originated with the production of Mon bricks and household utensils, later expanding to include piggy banks, water jars (nam ton), and vases. Over time, contemporary creativity was incorporated into the craft, leading to the creation of “smiling clay dolls,” which have become a distinctive symbol of local wisdom and an important source of economic income for the community. 2) The development of the pottery handicraft learning center through community participation revealed that the process was driven by the involvement of all community sectors. The main mechanism involved community focus group discussions that facilitated information exchange, problem analysis, co-design of development strategies, content and activity planning, and evaluation. The outcomes included the establishment of creative learning activities for children and youth, the strengthening of networks among producers and entrepreneurs, and the utilization of digital media to expand market opportunities. 3) The Guidelines for Promoting Pottery Handicraft Learning Centers through Community Participation in Banpatan, San Phak Wan Subdistrict, Hang Dong District, Chiang Mai Province. The study revealed that the proposed guidelines for promoting pottery handicraft learning centers align with contemporary social contexts. The key components are as follows: 1) Designing a contemporary learning center that integrates local wisdom with educational processes to communicate the stories and cultural values of pottery, thereby connecting learning with both everyday life and formal education. 2) Developing creative learning activities in the form of hands-on workshops and integration into formal education, employing digital media alongside traditional communication methods to engage diverse groups and broader society. 3) Establishing learning networks that connect the center with local economic activities and tourism development. 4) Creating high-quality, value-added pottery products to enhance the community’s economic resilience and sustainability and 5) Forming community enterprises to generate circulating income and strengthen long-term economic stability.